A COMPARATIVE STUDY OF GRADES 8 AND 9 STUDENTS’ BELIEFS TOWARDS TASK-BASED APPROACH AND TEACHER-CENTERED APPROACH IN TEACHING CHINESE AS A FOREIGN LANGUAGE CLASS AT A PRIVATE SCHOOL IN BANGKOK, THAILAND - WANG, SIWEI; ABEDIN FORHAD, MD. ZIAUL (Scholar: Human Sciences, 2022)
The purpose of this study was to investigate the levels of Grades 8 and 9 students’ beliefs as well as determine whether there was significant differences between task-based approach and teacher-centered approach in teaching Chinese as a foreign language class at a private school in Bangkok, Thailand. There were 92 Grade 8 and 90 Grade 9 participants as a population sample in the 2020-2021 academic year in this study. This research was designed as a quantitative comparative study. The students’ beliefs towards teaching approaches questionnaire from Zhang and Liu (2014) was used as the research instrument in this study. Descriptive statistic was utilized to analyze the levels of Grade 8 and Grade 9 students’ beliefs towards task-based approach and teacher-centered approach in teaching Chinese as a foreign language (CFL) class. Dependent samples t-test was used to compare whether there were significant differences between task-based approach and teacher-centered approach in teaching CFL class. The findings revealed that Grades 8 and 9 students expressed their positive beliefs towards task-based approach in teaching CFL class but showed their neutral belief towards teacher-centered approach. There was a significant difference in Grade 8 and Grade 9 students’ beliefs towards task-based and teacher-centered approaches in teaching CFL class. According to these findings, researcher provided some recommendations for students, Chinese teachers, school administrators, and future researchers.